ASSESSMENT OF HEAVY METALS ACCUMULATION AND ASSOCIATED HEALTH RISKS ON MORINGA OLEIFERA FROM SOUTHERN KADUNA, NIGERIA - Yawuck, Esther B.; Allems, G. A. (FUDMA JOURNAL OF SCIENCES, 2025)
Consuming medicinal herbs like Moringa oleifera that contains high levels of heavy metals can lead to major health issues. Moringa oleifera leaves obtained from Ambam (Jama’a LGA) and Maro (Kajuru LGA) in Kaduna State, Nigeria, were subjected to an AAS analysis to determine the content of heavy metals and associated health risk. Fe 7.627 mg/kg Pb 0.598 mg/kg, Ni 0.454 mg/kg, Mn 0.451 mg/kg, Zn 0.333 mg/kg, Cu 0.286 mg/kg, Cr 0.191 mg/kg were the order of metal concentrations in Moringa oleifera from Ambam. Maro metal concentrations trend follows a different order: Cd has the lowest concentration at 0.035 mg/kg, followed by Fe 3.453 mg/kg, Mn 0.601 mg/kg, Pb 0.505 mg/kg, Ni 0.327 mg/kg, Zn 0.262 mg/kg, Cu 0.221 mg/kg, and Cr 0.155 mg/kg. Ambam and Maro have Cd, Ni, and Mn concentrations below the WHO recommended acceptable range of 0.1 to 5.00 mg/kg. While Pb is over the WHO established permitted limit of 0.3mg/kg, the concentration of Cr in both Ambam and Maro was found to be within the limit of 0.2 to 2.0.3mg/kg. Consuming Moringa oleifera from this area may pose risk of cancer because the THQ values of Cd, Cu, Fe, Ni, and Pb were found to be greater than 1. The consumption of Moringa oleifera from the study regions may have a negative impact on the health of adult consumers, as indicated by the health index (HI) values of 43.7222 and 35.2028 at Ambam and Maro, respectively.